Nuclear factor I-A represses expression of the cell adhesion molecule L1 - Schneegans, Tanja (BioMed Central, 2009)
BACKGROUND: The neural cell adhesion molecule L1 plays a crucial role in development and plasticity of the nervous system. Neural cells thus require precise control of L1 expression. RESULTS: We identified a full binding site for nuclear factor I (NFI) transcription factors in the regulatory region of the mouse L1 gene. Electrophoretic mobility shift assay (EMSA) showed binding of nuclear factor I-A (NFI-A) to this site. Moreover, for a brain-specific isoform of NFI-A (NFI-A bs), we confirmed the interaction in vivo using chromatin immunoprecipitation (ChIP). Reporter gene assays showed that in neuroblastoma cells, overexpression of NFI-A bs repressed L1 expression threefold. CONCLUSION: Our findings suggest that NFI-A, in particular its brain-specific isoform, represses L1 gene expression, and might act as a second silencer of L1 in addition to the neural restrictive silencer factor (NRSF).